Development of Validated Stability-indicating RP-HPLC Method for Determination of Novel Directly Acting Antiviral agent and Characterization of its Degradants by LC–ESI–MS - Agarwal, Babita; Gandhi, Santosh (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The current study was performed to develop and validate stability indicating high performance liquid chromatography method (RP-HPLC) for determination of ledipasvir (LPR); to identify and characterize its major degradants by liquid chromatographic– tandem mass spectrometric method (LC-ESI-MS). Materials and Methods: The method was developed using reverse phase gradient elution and validated for standard ICH parameters. The optimized mobile phase comprised of acetonitrile:water with 0.2 % formic acid (70:30% v/v) at 1 ml/min flow rate with satisfactory retention time (tR), theoretical plates and good resolution of LPR and its degradants. Further, forced degradation under acid, base, thermal, photolytic and oxidative stress conditions was studied as per ICH guidelines. LC-ESI-MS with time of flight analyser was used to characterize the degradants. The degradation pathways for major degradants were proposed. Results: The developed method had retention time of 6 mins. The RSD for system was found to be less than 2% whereas mean recovery was obtained 97.2 – 102.5%. Linearity range of 5-30 μg/ml with 0.998 regression coefficient (R2) was observed. Detection and quantification limits were obtained as 0.010 μg/mL and 0.032 μg/mL, respectively. LPR was stable in photolytic and thermal environments whereas degraded in acid, base and oxidative states. LC–ESI–MS was used effectively for characterization and structural elucidation of degradants. Conclusion: The results indicated that validated RP-HPLC technique can be employed for routine analysis of LPR in bulk and dosage formulas and also would be capable of separating degradants from analyte peak.
Keywords: RP-HPLC; LC-ESI-MS; Ledipasvir; Stability indicating ICH method; Validation; Degradation pathway